Expression, regulation, and function of exosome‐derived miRNAs in cancer progression and therapy. Issue 10 (12th September 2021) - Li, Bowen; Cao, Yu; Sun, Mingjun; Feng, Hui
Abstract: Exosomes are a novel class of intercellular signal modulators that contain a wide range of molecules and deliver information between cells and tissues. MicroRNAs (miRNAs), a type of regulatory non‐coding RNA, are often incorporated into exosomes as signaling molecules. In this review, we discuss the expression of exosomal miRNAs from diverse origins such as tumor cells, solid tumor tissue, and biological fluids in various cancers (lung, breast, colorectal, liver, stomach, and pancreatic). We address the biological functions of exosome‐derived miRNAs in processes such as tumor‐cell proliferation, angiogenesis, metastasis, and chemoresistance in the tumor microenvironment. In particular, we discuss three oncogenic miRNAs, miR‐21, miR‐141, and miR‐451, which occur within exosomes, in terms of gene regulation and intercellular communication. We consider therapeutic miRNA‐based nanoparticles, which are widely expressed in tumors and show promise in drug therapy. The review assesses the wide‐ranging evidence for using exosomal miRNAs as tumor markers in molecular diagnosis. Further, we consider the use of nanoparticle platforms to transport miRNAs, in the targeted treatment of disease and tumors.